Diminishing signalling traffic for authentication in mobile communication system. (7th September 2004) - Lo, Chi-Chun; Sue, Kuen-Liang
In global system for mobile communication, the VLR requests the HLR for assistance in authenticating the visiting user. The authentication centre (AuC) in the home network generates 3-tuples and sends them back to the VLR for subsequent authentications during the user's residence. If these 3-tuples are used up before the MS's leaving, another request is issued by the VLR. The request is expensive, because it needs to access the HLR/AuC. Traditionally, a fixed-K strategy is used. That is, K 3-tuples are sent to the VLR for each request. However, much waste of 3-tuples is observed, especially when an inactive user is considered. Hence, we propose a dynamic-K (DK) strategy to reduce the waste and diminish the signalling traffic for authentication. Simulation results show that the DK strategy can effectively determine the appropriate K value. Not only the waste but also the number of requests is diminished efficiently.